ANNUAL CUMULATIVE OF SOIL CARBON CHANGE IN Pinus merkusii PLANTATION IN CIANTEN, WEST JAVA - Siringoringo, Harris Herman; Siregar, Chairil Anwar (Secretariat of Forestry Research and Development Agency, 2005)
Important carbon storage in a forest vegetation includes below ground carbon storage and above ground carbon storage. Carbon storage under the ground is higher than that above ground, so that soils are critical both as a source and sink of carbon. The main objective of this research is to examine the annual changes of soil carbon storage from year 2001 to year 2003 in the permanent plots of an experimental plantation (new plantation established in the year 2001) and in the permanent plots of control plot/baseline (young secondary forest), in Cianten Experimental Site, Bogor, West Java. Soil carbon content at 0-30 cm depth for 0 year old, 1 year old and 2 year old plantations are 4.14- 9.35%, 4.08 8.83% and 3.04- 7.61 %, respectively. Soil carbon content at control plot for 2001, 2002 and 2003 are 1.86-5.75%, 2.32 - 5.79% and 2.05 - 4.84%, respectively. Bulk density at 0-30 cm soil depth for 0 year old, 1 year old, and 2 yea.r old plantations are 0.38 - 0.5 mg/ m, 0.38 - 0.52% mg/ m3 and 0.32 - 0.5 mg/ m, respectively. Bulk density at control plot for 2001, 2002 and 2003 are 0.47 - 0.63 mg/m3, 0.43 -0.6 mg/m3 and 0.4 1- 0.55 mg/m3, respectively. The cumulative soil carbon stock of Pinus merkusii plantation is somewhat higher than that of baseline in Cianten Experimental Site, Bogor, West Java.